2009
DOI: 10.1007/s00418-009-0625-x
|View full text |Cite
|
Sign up to set email alerts
|

The inability of fully grown germinal vesicle stage oocyte cytoplasm to transcriptionally silence transferred transcribing nuclei

Abstract: For somatic cell nuclear transfer cytoplasts from metaphase II, oocytes are exclusively used. However, it is evident that certain reprogramming activities are present in oocytes even at earlier stages of maturation. These activities are, however, only poorly characterised. The main reason for this is that even the intrinsic oocyte processes are insufficiently understood. The mammalian oocyte is a highly specialised cell that harbours many specific characteristics. One of these is its particularly large size wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 34 publications
3
16
0
Order By: Relevance
“…2B), which was consistent with a previous report [23]. Although Fulka et al [24] recently reported that they were unable to detect unphosphorylated RPB1 in full-grown oocytes, this apparent discrepancy may have resulted from the anti-RPB1 CTD antibody they used for immunoblotting. The antibody they used reacts with both the phosphorylated and unphosphorylated forms of RPB1 but appears to have a much lower affinity for the unphosphorylated form.…”
Section: Discussionsupporting
confidence: 89%
“…2B), which was consistent with a previous report [23]. Although Fulka et al [24] recently reported that they were unable to detect unphosphorylated RPB1 in full-grown oocytes, this apparent discrepancy may have resulted from the anti-RPB1 CTD antibody they used for immunoblotting. The antibody they used reacts with both the phosphorylated and unphosphorylated forms of RPB1 but appears to have a much lower affinity for the unphosphorylated form.…”
Section: Discussionsupporting
confidence: 89%
“…Similar studies were previously performed in the mouse (Fulka et al, 2009; Abe et al, 2010), but the authors interpreted their results differently. Fulka et al (2009) concluded that RNA polymerase II is degraded during oocyte growth. The authors also used the CTD4H8 and 8WG16 clones for immunofluorescence and Western blots.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, the dephosphorylation of POLR2A was followed by the release of RNA polymerase II from DNA (Abe et al, 2010). The findings of Abe et al (2010) are in contrast to the study by Fulka et al (2009), who did not observe any form of RNA polymerase II in fully grown, mouse GV oocytes, and therefore concluded that the RNA polymerase II is degraded in these cells (Fulka et al, 2009).…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Upon follicular recruitment, the oocyte enters the growth phase and after completing the growth phase the oocyte becomes transcriptionally inactive (Mehlmann 2005). Fulka et al (2009) used an oocyte fusion model to determine if the fully grown germinal vesicle stage oocyte could induce suppression of transcription activity in transcribing germinal vesicle stage oocytes. Although the authors identiWed mechanisms for silencing transcription, such as RNA polymerase II degradation and rearrangement of splicing proteins in mature oocytes, these oocytes were insuYcient to induce these changes in transcriptionally active nuclei, which led the authors to discuss the selection of cytoplasts in nuclear transfer experiments.…”
Section: Female Reproductive Systemmentioning
confidence: 99%